Scaffolding-Enhanced Problem-Based Learning to Improve Civic Education Students' Conceptual Mastery - Nurmalisa, Yunisca; Pitoewas, Berchah; Nurhayati; Purwantiningsih, Ary; Sari, Dian Permata (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examined whether a scaffolding-enhanced Problem-Based Learning (PBL) strategy delivered in a blended learning format was associated with higher civic conceptual mastery among undergraduate civic education students. A quasi-experimental pretest-posttest nonequivalent control-group design with a 2 x 2 factorial arrangement was implemented with 70 students from the Department of Civic Education, Faculty of Teacher Training and Education, Universitas Lampung. The experimental class received scaffolding-enhanced PBL supported by face-to-face problem-solving activities, structured prompts, guiding questions, visual organizers, formative feedback, and online learning resources. The control class received conventional PBL without the explicit scaffold package. Students were classified into high and low initial-ability groups before the intervention. N-gain scores were analyzed using two-way ANOVA and exploratory LSD follow-up comparisons. The results showed a significant main effect of instructional strategy, F(1, 66) = 9.281, p = .003, partial eta squared = .123, and a stronger main effect of initial ability, F(1, 66) = 66.167, p < .001, partial eta squared = .501. The strategy x initial ability interaction was not significant, F(1, 66) = 2.393, p = .127. By the third meeting, 71.43% of students in the experimental class reached the high N-gain category, compared with 22.86% in the control class. The findings suggest that scaffolding can strengthen PBL for civic conceptual mastery, but the nonsignificant interaction and low-ability comparison indicate that more differentiated scaffolding is needed for students who enter the course with weaker prior knowledge.